Retinal sublayer defect is independently associated with the severity of hypertensive white matter hyperintensity. Issue 2 (25th December 2019) - Qu, Man; Kwapong, William Robert; Peng, Chenlei; Cao, Yungang; Lu, Fan; Shen, Meixiao; Han, Zhao
Abstract: Purpose: To investigate the association of specific retinal sublayer thicknesses on optical coherence tomography (OCT) imaging with brain magnetic resonance imaging (MRI) markers using the Fazekas scale in hypertensive white matter hyperintensity (WMH) subjects. Methods: Eighty‐eight participants (32 healthy controls and 56 hypertensive white matter hyperintensity subjects) underwent retinal imaging using the OCT and MRI. A custom‐built algorithm was used to measure the thicknesses of the retinal nerve fiber layer (RNFL) and ganglion cell layer and inner plexiform layer (GCIP). Focal markers for white matter hyperintensities were assessed on MRI and graded using the Fazekas visual rating. Results: Hypertensive WMH showed significantly reduced ( p  < .05) RNFL and GCIP layers when compared to healthy controls, respectively. A significant correlation was found between the RNFL ( ρ  = −.246, p  < .001) and GCIP ( ρ  = −.338, p  < .001) of the total participants and the Fazekas score, respectively. Statistical differences were still significant ( p  < .05) when correlations were adjusted for intereye correlation, age, hypertension, smoking, body mass index, and diabetes. Among the cases of hypertensive WMH, higher Fazekas scores were significantly associated ( p  < .05) with the thinning of both the RNFL and GCIP layers after adjustment of age and other risk factors. Conclusions: Retinal degeneration in the RNFL and GCIP was independently associated with focal lesions in the white matter of the brain and deteriorates with the severity of the lesions. We suggest that imaging and measurement of the retinal sublayers using the OCT may provide evidence on neurodegeneration in WMH. Abstract : In our current study, we conducted an observational study to investigate the association of the retinal sublayer thickness on OCT with focal markers of brain tissue on MRI in participants with WMH using the Fazekas scale. Retinal degeneration in the RNFL and GCIP was independently associated with focal lesions in the white matter of the brain and deteriorates with the severity of the lesions. We suggest that imaging and measurement of the retinal sublayers using the OCT may provide evidence on neurodegeneration in WMH.